Photosynthesis in rice is increased by CRISPR/Cas9-mediated transformation of two truncated light-harvesting antenna - Caddell, Daniel; Langenfeld, Noah J.; Eckels, Madigan JH.; Zhen, Shuyang; Klaras, Rachel; Mishra, Laxmi; Bugbee, Bruce; Coleman-Derr, Devin (Frontiers in Plant Science, 2023)
Plants compete for light partly by over-producing chlorophyll in leaves. The resulting high light absorption is an effective strategy for outcompeting neighbors in mixed communities, but it prevents light transmission to lower leaves and limits photosynthesis in dense agricultural canopies. We used a CRISPR/Cas9-mediated approach to engineer rice plants with truncated light-harvesting antenna (TLA) via knockout mutations to individual antenna assembly component genes CpSRP43, CpSRP54a, and its paralog, CpSRP54b. We compared the photosynthetic contributions of these components in rice by studying the growth rates of whole plants, quantum yield of photosynthesis, chlorophyll density and distribution, and phenotypic abnormalities. Mutations in any of these three genes involved in antenna assembly decreased chlorophyll content and light absorption and increased photosynthesis per photon absorbed (quantum yield). Additionally, we investigated a Poales-specific duplication of CpSRP54. The Poales are an important family that includes staple crops such as rice, wheat, corn, millet, and sorghum. These results have significant implications for the improvement of high leaf-area-index crop monocultures.